Intelligibility of Polish and German speech for the Polish audience in the presence of noise - HOJAN, E.; FASTL, H. (Archives of Acoustics, 2014)
The ability of Polish listeners to understand Polish in the presence of two different noises, the Fastl noise and CCITT Rec. 227 noise was measured. The Speech Perception in Noise SPIN test was administered at 68 dB SPL to 10 normal listeners. The results are compared with those of similar experiments done for German. In the case of CCITT noise, most of the listeners have more difficulty to understand both Polish and German.